2023
DOI: 10.3390/su15042931
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Consumers’ Barriers to Using FinTech Services in the United Arab Emirates: Mixed-Methods Research Approach

Abstract: The cutting-edge development known as FinTech is now fast replacing traditional financial services all over the world. Despite that, UAE consumers are still not embracing FinTech services at the expected rate. This study hence suggests expanded research based on the unified theory of acceptance and use of technology (UTAUT) to deeply examine the obstacles preventing consumers from using FinTech services. This research utilised an exploratory sequential mixed-method approach. Preliminary semi-structured intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 114 publications
4
8
0
Order By: Relevance
“…This is due to the fact that the latter is not an appropriate proxy for consumption, since not all purchases involve personal consumption, whereas all consumption is accompanied by a purchase and is viewed as significantly related to the product, as previously discussed. This is in accordance with the recommendation by [19,[76][77][78] to not combine actual behaviour and intention cases' responses as their patterns are distinct. A self-administered questionnaire was employed for collecting data in this research using the drop-off and collect approach.…”
Section: Methodssupporting
confidence: 90%
“…This is due to the fact that the latter is not an appropriate proxy for consumption, since not all purchases involve personal consumption, whereas all consumption is accompanied by a purchase and is viewed as significantly related to the product, as previously discussed. This is in accordance with the recommendation by [19,[76][77][78] to not combine actual behaviour and intention cases' responses as their patterns are distinct. A self-administered questionnaire was employed for collecting data in this research using the drop-off and collect approach.…”
Section: Methodssupporting
confidence: 90%
“…Previous research conducted by Amanah, Rahadian, and Iradianty (2016) found that financial attitude partially affects financial management behavior. Similar findings have been made by Mien and Thao (2015) and Herdjiono and Damanik (2016) regarding the favorable influence of financial attitude on financial management behavior, which also extends to the adoption and management of fintech (Bouteraa, Chekima, Lajuni, & Anwar, 2023). Based on these findings, it is hypothesized that:…”
Section: Financial Attitudesupporting
confidence: 65%
“…Corruption's adverse effects on economic growth manifest through indirect channels, impacting areas such as investment, education, trade policy, and political stability (Bouteraa, Chekima, Lajuni, & Anwar, 2023). Pellegrini and Gerlagh (2004) demonstrated that corruption inhibits economic growth by 19%.…”
Section: Corruption Hinders Economic Growthmentioning
confidence: 99%